Dos terreiros para as avenidas: uma análise política sobre as lideranças dos afoxés em Sergipe - Santos, Liliane Maria de Santana (2013)
This dissertation has the afoxés sergipanos as the object of study, we seek to understand it relation to the partisan politics. To do so, we anilyze the political context in wich the afoxé emerged, the relation between this context and the political leadership and how it is vinculated to the politicians, such as afoxés and candomblé s relation showing thru rituals that there is an inequality between the afoxés and the sergipe political partisan. The central question of this study consisted in discovering wich relations exist between the afoxés and the sergipe political partisan. Thus, the central teme of this work is the relation between the sergipeans afoxés and municipal and state partisan politics. I analyse the process of emergence and development of the afoxés in Sergipe among the political context of brazilian democratization and the political oportunities that were criated by this context enabling the emergence of the afoxés in this state. The research had as a teorical and methodological orientation the use of reference that combine assumptions of anthropology and theoris of social movements, as well as the use of ethnografy as the major factor for the development of this analysis providing the participant observation, enterviews and the aprehension of the existing rituals in the afoxés. The results demonstrate the favorable conditions for the emergence of the afoxés among the sergipean politics relations, namily, the political oportunities and the social relations network that make possible the needed articulation for this process.